The impact of the model and follows on the collection and Retention of fifth grade students (oiterary) in history (Journal Of Educational and Psychological Researches, 2016)
The first chapter the importance of research and need for education scientists see that the roots of the use of a specimen Wheatley in learning and teaching back to Grayson Wheatley, one of the largest supporters of a modern construction, which lay the groundwork for the specimen stage and the form in which it is. That was attributed to him, often called his name called while some educators based learning strategy on the issue. He sees the learner in this model make him a meaningful understanding of problems during his progress, thereby acting with his colleagues to find solutions to them in small groups. He         Borders Search: Search by students is determined by the current fifth grade (literary) in high school and junior high in Baghdad governorate / center        Chapter II of Arab studies and foreignStudies on the model followed in the collection and retention        Chapter III experimental design: researcher determined experimentally adopted a two experimental and control groupRewarded researcher b prior knowledge test,Research tools to prepare for the test after the collection of statistical procedures in terms of difficulty and discriminationAfter the completion of the requirements of the experiment, the search experience began on Sunday, 08.10.2014 dish and post test to acquire a historical concepts Wednesday, 12/17/2013, and thus the search experience ended in the retention test article after (21) days from the end of the experiment        Chapter IV presented in this chapter the researcher's findings on according to objective research and hypotheses rejected FrdahseatThe results showed that there are significant differences between the two groups differences degrees studentsConclusions- The specimen is followed by a new strategy led to increased attention and looking forward to the students of history, and increased the desire to know the course material and prepare them for herRecommendations - Encourage and train  students on the specimen is followed and get them used Proposalssimilar study procedures for various stages of the variable sex-- study reveals the impact of a prototypical followed on critical and creative thinking